Jalur Trotoar Responsif Penyandang Low Vision: Studi Kasus Pasar Baru Bandung - Sally Octaviana (PLD UIN Sunan Kalijaga, 2019)
Sidewalks are public facilities and must be accessible to all users. This study departs from the lack of quality of public open space in Bandung and the absence of a sidewalk model that is responsive to people with low vision. The purpose of this research is to find out the design principles and to make responsive pavement design models of people with low vision. Data was collected by interviewing and observing the behavior and travel of people with low vision on some familiar and unfamiliar sidewalks in the city of Bandung. Data analysis was carried out from recorded interviews to find out the obstacles faced by people with low vision when exploring sidewalk space. This research produces criteria and models of pavement design that are responsive to persons with a low vision based on their limitations. The results of the study are expected to contribute to the concept of pavement design so that people with low vision can have equal and independent rights in accessing public space[Trotoar adalah fasilitas publik dan harus aksesibel bagi semua penggunanya. Penelitian ini berangkat dari kurangnya kualitas ruang terbuka publik di Bandung dan belum adanya model trotoar yang responsif terhadap penyandang low vision. Tujuan penelitian untuk mengetahui prinsip-prinsip perancangan dan membuat model perancangan trotoar responsif penyandang low vision. Data dikumpulkan dengan wawancara dan observasi terhadap perilaku dan perjalanan penyandang low vision di beberapa trotoar yang familier dan tidak familier di Kota Bandung. Analisis data dilakukan dari rekaman hasil wawancara untuk mengetahui hambatan yang dihadapi penyandang low vision ketika menjelajah ruang trotoar. Penelitian ini menghasilkan kriteria dan model perancangan trotoar yang responsif penyandang low vision berdasarkan keterbatasan yang dimiliki oleh mereka. Hasil penelitian diharapkan berkontribusi dalam konsep perancangan trotoar agar penyandang low vision dapat memiliki hak setara dan mandiri dalam mengakses ruang publik.]